Religious Truth for Our Time - Watt, W. Montgomery (William Montgomery) (Oxford A Oneworld Book, 1995)
Offering ways of addressing the intellectual and practical problems confronting today's religions, this study discusses the way forward for those who believe in the importance of religious faith in a multi-religious world.
Keywords: Christianity and other religions. Religions -- Relations. Religion and culture. Interfaith relations. Religions. Religion